2015
DOI: 10.2147/copd.s73521
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire on switching from the tiotropium HandiHaler to the Respimat inhaler in patients with chronic obstructive pulmonary disease: changes in handling and preferences immediately and several years after the switch

Abstract: Background Tiotropium (Spiriva) is an inhaled muscarinic antagonist for patients with chronic obstructive pulmonary disease (COPD), and is available in two forms: the HandiHaler and the Respimat inhaler. The aim of this study was to investigate the handling of and preference for each device immediately after switching from the HandiHaler to the Respimat and 2–3 years after the switch. Materials and methods The study comprised two surveys. A questionnaire was first admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In a follow-up study, 2–3 years later, the proportion of patients who expressed a preference for Respimat ® had significantly increased to 80% ( P <0.0001) 55. The different responses obtained during the first and second surveys may suggest that the change in inhaler device was stressful for the patients.…”
Section: Components Of Patient Preference and Satisfaction With Inhalersmentioning
confidence: 96%
See 2 more Smart Citations
“…In a follow-up study, 2–3 years later, the proportion of patients who expressed a preference for Respimat ® had significantly increased to 80% ( P <0.0001) 55. The different responses obtained during the first and second surveys may suggest that the change in inhaler device was stressful for the patients.…”
Section: Components Of Patient Preference and Satisfaction With Inhalersmentioning
confidence: 96%
“…One survey of patients with COPD suggested that Respimat ® had a significantly milder aftertaste than HandiHaler ® , but there were no significant differences between the incidence of surveyed adverse events, including dry mouth and throat-related side effects 55. In another survey, Respimat ® was associated with increased incidence of cough within the first 4 weeks of switching from HandiHaler ® ; however, this was transient and most patients overcame having a cough as they got used to using Respimat ® 41…”
Section: Components Of Patient Preference and Satisfaction With Inhalersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the disadvantages of the HandiHaler are: a) the need to place an individual capsule into the device immediately before each use, b) the need to discard the spent capsule and to clean the device and remove remnants of the hard gelatin capsule after each use, c) potential hygiene problems from the need to repeat the loading and cleaning steps, and d) difficulty of using the device by patients with impaired dexterity 19,28. Another disadvantage is that a patient’s inspiratory effort affects powder dispersion, and the operational complexity of the device can make it challenging to generate sufficient fine particles to ensure proper drug deposition in the lower airway in the elderly and patients with more severe airway obstruction 28,30.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rise of error rates in use of inhalation devices with increasing age,35 easy-to-use multidose DPIs are considered as especially beneficial for elderly COPD patients because they can improve patient adherence to treatment and thereby improve long-term outcome 19,36…”
Section: Introductionmentioning
confidence: 99%